KAJIAN HUKUM TERHADAP REPRESENTASI KEPEMIMPINAN WANITA SEBAGAI WUJUD BIROKRASI YANG PROFESIONAL - Riski Febria Nurita (Jurnal Cakrawala Hukum, 2017)
Convention on the Elimination of All Forms of Discrimination Against Women 1979, has ratified Indonesia as the Law of the Republic of Indonesia Number 7 Year 1984 About Ratification of the Convention Concerning the Elimination of All Forms of Discrimination Against Women. In relation to the ratification of the Convention on Women, among others, means to promote the widest possible extent of women’s rights, Indonesia guarantees for women, on equal terms with men, to protect their rights. This research focuses on legal studies related to the impact of the ratification in realizing the contribution of women’s role in contribution. The method used is the approach of law and case approach to solve the problem of women’s leadership representation as a professional bureaucracy after Indonesia ratified the women’s convention. The form of implementation of the law which is the ratification of the international women convention is not implemented in every life of the nation and state, there are still many misuse and injustice to the role of women in bureaucracy in Indonesia. The ratification requires the government to prioritize the right of women as leaders to realize a professional bureaucracy.DOI: https://doi.org/10.26905/idjch.v8i2.1675